DAMPAK CYBERBULLYING PADA ATLET : STUDI LITERATUR - Iffah Rosyiana; Dimas Aditya Syaukani (Universitas Muhammadiyah Surabaya, 2025)
Cyberbullying among athletes has emerged as a critical issue in the context of increasing social media engagement within the sports community. This literature review explores the psychological risks posed by online harassment on platforms such as Instagram and Twitter, emphasizing its detrimental effects on both amateur and professional athletes. Drawing on national journals from the past three years, peer-reviewed academic articles, and institutional reports, the study reveals that cyberbullying significantly contributes to mental health challenges, including social anxiety, diminished self-esteem, and reduced athletic performance. Key contributing factors include heightened public expectations, emotional regulation difficulties, and the anonymity afforded to perpetrators. To address these challenges, the literature highlights several mitigation strategies, such as implementing hate speech detection technologies, enhancing digital literacy, promoting awareness of athletes’ mental health, and fostering collaboration between legal authorities, social media companies, and sports organizations. This review underscores the importance of mental health protection for athletes in the digital era and advocates for the development of digital literacy policies that incorporate psychological well-being as a central concern.